Training Curriculum Development for Enhancing Entrepreneurship Learning Management Abilities of Vocational College Lecturers in Henan Province, People’s Republic of China - Liu , Ling; Buranaphansak, Ketsuda; Prachanan, Nawamin (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background: The Chinese economy is in the stage of recovery during the post-pandemic period. There are two forms of recovery, the first being that the Chinese economy maintains a "stable" trend; The second form is manifested in the fact that the foundation of recovery is not stable enough and has imbalanced characteristics. One of the problems is the high employment pressure. College graduates have an absolute advantage in the pressure sources for employment. This study aims to study, analyze, develop, and evaluate the training curriculum for enhancing entrepreneurship learning management abilities of vocational college lecturers in Henan province. Methods: This research paper follows the mixed-methods design. The samples in this research were 365 vocational college teachers, 398 vocational college students, and 390 vocational college graduates from 5 vocational colleges in Nanyang City, Henan Province. A questionnaire was used as an instrument for gathering data in the present investigation. The obtained data were analyzed by using frequency, percentage, mean, and standard deviation. A semi-structured interview was analyzed by using the content analysis technique. The test scores were calculated to find out the mean and standard deviation. A dependent samples t-test was used to compare the test mean scores after the training program to detect a significant difference at the .05 level. The collected data were analyzed by using the mean and standard deviation. Results: This study developed and evaluated a training curriculum to enhance the entrepreneurship learning management abilities of vocational college lecturers in Henan Province, People’s Republic of China. Using a mixed-methods approach, findings revealed high levels of entrepreneurial skills post-training, with significant improvements in knowledge, innovation, and motivation. Conclusion: The research shows that at high levels of the lecturers of entrepreneurship have learning management abilities in Henan Province. It emphasizes factors such as entrepreneurship knowledge, innovative thinking, and entrepreneurship motivation, and highlights the importance of the training curriculum for improving entrepreneurship learning management abilities of lecturers in vocational colleges.